2008
DOI: 10.1111/j.1365-2753.2007.00864.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of occupational violence on Australian general practitioners’ provision of home visits and after‐hours care: a cross‐sectional study

Abstract: This study's finding of GPs' self-reported restriction of practice and withdrawal from home visits and after-hours calls in response to risk of violence represents a significant primary health care issue. GPs' decision to provide after-hours calls and home visits is complex, and the finding of lack of significant association of experiences of violence with provision of home visits and after-hours calls is likely to be due to the cross-sectional nature of the study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 16 publications
1
28
1
1
Order By: Relevance
“…Comparisons to studies that looked at regular‐hour Australian general practices, however, indicate that this 47.1% rate from this work is relatively low, as exemplified by the 63.7% and 59.3% recorded in 2 different New South Wales (NSW) studies, as well as the 57% rate recorded in Victoria . Our finding is equally less than the estimated two‐thirds aggression‐rate suggested by the Royal Australian College of General Practitioners (RACGP) as the prevalent rate among Australian GPs, but is nearly identical to the 48% prevalence rate recorded among hospital‐based doctors in a 2004 survey of health care staff in northern NSW …”
Section: Discussioncontrasting
confidence: 42%
See 1 more Smart Citation
“…Comparisons to studies that looked at regular‐hour Australian general practices, however, indicate that this 47.1% rate from this work is relatively low, as exemplified by the 63.7% and 59.3% recorded in 2 different New South Wales (NSW) studies, as well as the 57% rate recorded in Victoria . Our finding is equally less than the estimated two‐thirds aggression‐rate suggested by the Royal Australian College of General Practitioners (RACGP) as the prevalent rate among Australian GPs, but is nearly identical to the 48% prevalence rate recorded among hospital‐based doctors in a 2004 survey of health care staff in northern NSW …”
Section: Discussioncontrasting
confidence: 42%
“…To calculate the minimum number of responses required to reflect the desired statistic in this study, an estimation was done based on a previous study 21 that found a 63.7% aggression-rate among doctors. With a population size of 300 in this study, and allowing for an error margin of 5% with a 95% confidence interval (CI), the minimum required number of responses was found to be 163.…”
Section: Sample Size Estimationmentioning
confidence: 99%
“…Occupational violence is a major issue in general practice in Australia and internationally, with effects both on the individual and their provision of services to patients [54,55]. There is some evidence that GP registrars, particularly rural registrars, are at particular risk of occupational violence and its effects [56].…”
Section: Discussionmentioning
confidence: 99%
“…Noen leger er bekymret for egen sikkerhet, spesielt i møte med pasienter som er så ruspåvirket eller psykisk syke at deres atferd oppleves uforutsigbar (Johansen, Carlsen & Hunskaar, 2011). Internasjonal forskning tyder på at bekymring for egen sikkerhet reduserer legenes villighet til å delta i vakt (Magin, Adams & Ireland, 2005;Magin, Adams & Sibbritt, 2008;Hobbs, 1994). Mange steder i Norge er legevaktpersonell alene hele eller deler av døgnet, uten at det nød-vendigvis er iverksatt adekvate sikkerhetstiltak (Morken & Johansen, 2013).…”
Section: Ambulansetjenesten Og Bruk Av Politiunclassified